2008
DOI: 10.1158/0008-5472.can-08-2103
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7, a Homeobox D10 Target, Inhibits p21-Activated Kinase 1 and Regulates Its Functions

Abstract: MicroRNAs (miRs) are non-coding RNAs that inhibit expression of their targets in a sequence-specific manner and play crucial roles during oncogenesis. Here we show that miR-7 inhibits p21-activated kinase 1 (Pak1) expression, a widely upregulated signaling kinase in multiple human cancers including breast and gliomas, by targeting the 3′-UTR of Pak1 mRNA. We noticed an inverse correlation between the levels of endogenous miR-7 and Pak1 expression in human cancer cells. We discovered that endogenous miR-7 expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
196
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(212 citation statements)
references
References 20 publications
14
196
0
2
Order By: Relevance
“…It has been reported that miR-7 has a tumorsuppressor role in various cancers including brain tumors, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009), and we herein showed that miR-7 also functions as a tumor suppressor in gastric cancer. Interestingly, in the normal stomach, miR-7 expression is induced during the differentiation of gastric epithelial cells, suggesting a role of miR-7 in the regulation of epithelial cell differentiation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It has been reported that miR-7 has a tumorsuppressor role in various cancers including brain tumors, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009), and we herein showed that miR-7 also functions as a tumor suppressor in gastric cancer. Interestingly, in the normal stomach, miR-7 expression is induced during the differentiation of gastric epithelial cells, suggesting a role of miR-7 in the regulation of epithelial cell differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…We found the expression level of miR-7 to significantly decrease in gastric tumors in an inflammation-dependent manner. It has been shown that miR-7 has a tumor-suppressor role in several cancers, including glioblastoma, breast cancer and lung cancer (Kefas et al, 2008;Reddy et al, 2008;Webster et al, 2009;Jiang et al, 2010;Saydam et al, 2011). In this manuscript, we demonstrate that miR-7 is induced during the differentiation of normal gastric epithelial cells, and it also has a tumor-suppressor role in the stomach.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…In addition, it still positively regulates miR-7 (Reddy et al, 2008), which was found to control epidermal growth factor receptor signaling and promote photoreceptor differentiation, inducing cell cycle arrest and cell death in some cancer cell lines (Kefas et al, 2008;Webster et al, 2009). miRNA expression profiling revealed that miR-7 was involved in tumor aggressiveness, invasion and metastasis in urothelial carcinomas and breast cancer (Foekens et al, 2008;Veerla et al, 2009).…”
Section: Pro-metastatic Mirnas Regulate Tumor Metastasismentioning
confidence: 99%
“…miRNA expression profiling revealed that miR-7 was involved in tumor aggressiveness, invasion and metastasis in urothelial carcinomas and breast cancer (Foekens et al, 2008;Veerla et al, 2009). Reddy et al (2008) found that miR-7 inhibited p21-activated kinase 1 (Pak1) that has the potential to promote tumor invasion and metastasis. Accordingly, the HoxD10/miR-7/Pak1 and BRMS1/Twist/miR-10b/HOXD10/RHOC pathways form a cascade effect for tumor metastasis (Figure 2).…”
Section: Pro-metastatic Mirnas Regulate Tumor Metastasismentioning
confidence: 99%